1999
DOI: 10.1088/0022-3727/32/8/016
|View full text |Cite
|
Sign up to set email alerts
|

An analytical model for the laser drilling of metals with absorption within the vapour

Abstract: A mathematical model for the laser drilling of metals is given for the cases of constant and pulsed laser sources. Attenuation of the laser beam within the vapour is considered through an averaged absorption coefficient . The experimentally observed logarithmic dependence of the hole depth on the laser energy is predicted theoretically. A singular perturbation technique is used in order to find solutions valid for different regimes of time, namely pre-vaporization and post-vaporization times. Uniformly valid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 9 publications
(17 reference statements)
0
35
0
Order By: Relevance
“…It is possible to estimate from (2) the important parameter q (2) c of any kind of heat action, where q (2) c is the critical density of the laser radiation flux, at which the metal surface reaches the boiling temperature T b . The relation between q (2) c and q 0 allows us to estimate the level of intensity for the metal evaporation under the action of the laser radiation pulse.…”
Section: Formation Of Holes By Laser Radiationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible to estimate from (2) the important parameter q (2) c of any kind of heat action, where q (2) c is the critical density of the laser radiation flux, at which the metal surface reaches the boiling temperature T b . The relation between q (2) c and q 0 allows us to estimate the level of intensity for the metal evaporation under the action of the laser radiation pulse.…”
Section: Formation Of Holes By Laser Radiationmentioning
confidence: 99%
“…The laser processing, with the radiation flux density more than the critical q (2) c , is accompanied by fusion, material evaporation, and also by the emission of fragments of substance (matter) in a solid phase. The formation and scattering of destruction products is observed at the beginning of the action of the laser pulse with the radiation flux density 10 6 -10 9 W/cm 2 [15].…”
Section: Formation Of Holes By Laser Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Biswas et al used an ANN-based model of laser drilling of 0.496 mm thick titanium nitride-alumina (TiN-Al2O3) composite to investigate the effect of input variables (pulse frequency, lamp current , pulse width, assist gas pressure and focal length) on output parameters (circularity at entrance hole and exit hole, hole taper). Mathematical model for laser drilling process, which calculated the effect of laser absorption by the metal vapor in the keyhole, was investigated by Solana et al (Solana et al, 1998). They used this model to simulate the hole, and the data were in good agreement with experimental results.…”
Section: Introductionmentioning
confidence: 96%
“…The ablation phenomenon with repetitive irradiation is more complicated than single-pulse irradiation onto a planer ablator because the crater, which is generated and deformed with the pulse number at the ablation area, influences the impulse. Solana et al 8) reported that, with a plate thicker than 1 mm, the laser energy necessary for piercing logarithmically increases as the thickness increases. This result is based on both experimental and numerical studies and suggests that the ablated mass per single pulse is decreased due to crater deepening.…”
Section: Introductionmentioning
confidence: 99%